LAMELAR CORNEAL TRANSPLANTATION IN A DOG FOR SURGICAL TREATMENT OF CORNEA DEEP ULCER WITH DESCEMETOCELE. - Guimarães, T. (2018)
Corneal transplantation is a procedure indicated for surgical treatment of several corneal diseases, requiring replacement of the affected tissues1,2,3,4. A dog of undefined breed, 5 years old, revealed on ocular examination, a deep corneal ulcer and a Descemet\'s membrane (DM) exposure. Aiming at corneal repair, the surgical technique of lamellar corneal transplantation was used. The perimeter of the transplant was defined with the help of a biopsy punch. With a 1 ml syringe and a 26 G” needle, air was injected into the deep corneal stroma in order to separate DM from stroma1,2. Subsequently paracentesis was performed to reduce ocular pressure and a small air bubble was added in order to help the corneal depthness perspective. With a crescent knife, excision of the compromised tissue was performed1,3. The DM was covered using cryopreserved canine cornea4 at -20°C in 3mg/ml tobramycin solution and thawed at room temperature it was also molded obtaining the appropriate sized tissue for the recoil1. The corneal suture was made using simple isolated points with 8-0 polyglactin and for corneal protection a third eyelid flap was performed1,3. Topical moxifloxacin, tropicamide, EDTA and autologous serum were used in post-surgical treatment3. The third eyelid flap was removed at 15 days post-surgery and a complete corneal repair was observed with total incorporation in the recipient cornea. Lamellar corneal transplantation employing cryopreserved cornea in tobramycin solution has been shown to be effective in the surgical treatment of descemetocele when related to other techniques1,3,4.